Pedagogy and Human Rights Perspective What Teachers have to Say? - Sandeep Kumar (JOURNAL OF INDIAN EDUCATION, 2021)
Education is expected to develop a cohesive and peaceful society and for this, various perspectives exist which rely upon the role of education to achieve this objective. Contribution of education can be envisioned via school and school practices, in which pedagogy is one of the imperative aspects, where children unswervingly interact with each other. But, how a teacher perceives teachinglearning process is also significant. We know that providing equal opportunities, mutual respect, democratic environment etc. definitely subsidises positively to the idea of pedagogy. Coalescing pedagogy and human rights perspective provides a new avenue to develop human rights perspective based pedagogy, which can contribute significantly in teaching learning process in school to achieve a larger objective of creating our society a ‘humane society’. But, this objective cannot be achieved unless teachers develop sensitivity toward this blending. Hence, the present paper explores the teachers’ understanding about human rights and human rights perspective based pedagogy.